2007
DOI: 10.1111/j.1467-9922.2007.00399.x
|View full text |Cite
|
Sign up to set email alerts
|

Japanese Language Students' Perceptions on Kanji Learning and Their Relationship to Novel Kanji Word Learning Ability

Abstract: This study examines the relationship between how learners of Japanese as a second language perceive the learning of kanji (i.e., the logographic characters shared with Chinese) and their ability to learn novel kanji words using morphological and contextual information. Eighty college students learning Japanese as a foreign language completed a 60-item kanji questionnaire, a 75-item kanji test, and a 30-item reading comprehension test. Results indicated modest but statistically significant correlations between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 68 publications
(94 reference statements)
0
16
0
1
Order By: Relevance
“…The studies outlined above only examined students' own view of their learning strategies, so Mori, Sato & Shimizu (2007) explored the relationship between students' perceptions and their actual use of strategies in handling novel kanji words. The results indicated that belief in the effectiveness of metacognitive strategies could predict success in the compositional analysis of novel kanji characters/words, suggesting that enhancing students' metacognitive awareness may increase their chances of becoming strategic kanji learners.…”
Section: Vocabulary and Kanji Learningmentioning
confidence: 99%
“…The studies outlined above only examined students' own view of their learning strategies, so Mori, Sato & Shimizu (2007) explored the relationship between students' perceptions and their actual use of strategies in handling novel kanji words. The results indicated that belief in the effectiveness of metacognitive strategies could predict success in the compositional analysis of novel kanji characters/words, suggesting that enhancing students' metacognitive awareness may increase their chances of becoming strategic kanji learners.…”
Section: Vocabulary and Kanji Learningmentioning
confidence: 99%
“…walking, running, and weightlifting) using the equipment provided, hence, K2 (Kanji and Katakana) gym. Various researchers have reported on the Kanji learning strategies adopted by learners from different linguistic backgrounds (Kato 2005;Mori, Sato, and Shimizu 2007;. Of various strategies reviewed, rote learning was frequently employed and both students and instructors considered it to be the most effective learning/teaching strategy (e.g.…”
Section: K2 (Kanji and Katakana) Gymmentioning
confidence: 99%
“…Gamage 2003;Ishida 1989;Iwashita and Sekiguchi 2009;Mori 1999;Mori, Sato, and Shimizu 2007;Toyoda 1998). The difficulty of Kanji is not limited to its writing, but extends to its reading as pointed out by many educators and researchers.…”
Section: Introductionmentioning
confidence: 96%
“…As a result, a large portion of kanji instruction must often be completed independently, and testing is used as the only measure of what students have learned outside of class. Such limited instruction may account for the overreliance on rote memorization observed among many L2 Japanese students (Mori, Sato, & Shimizu, ; Mori & Shimizu, ). While there is nothing wrong with rote learning, the lack of flexibility in strategy use and the lack of self‐monitoring eventually make it difficult to continue to learn kanji effectively (Mori, ; Rose & Harbon, ; Wang, Spencer, & Xing, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other studies have consistently demonstrated that the use of multiple sources of information leads to better learning than reliance on a single source of information (Mori, , ; Shen, ). Available strategies include compositional analysis (Jackson, Everson, & Ke, ; Kubota & Toyoda, ; Mori, ; Mori et al, ; Shen & Ke, , Toyoda, ; Yamashita & Maru, ), context‐based strategies (Kondo‐Brown, ; Mori, , Mori & Nagy, ; Taniuchi & Komori, ; Yamagata, ), mnemonic strategies (Kuo & Hooper, ; Kuwabara, ; Rose, ; Soemer & Schwan, ; Toyoda & McNamara, ; Verhaeghen, Palfai, & Johnson, ), and repeated writing (Butler, ; Gamage, , Nesbitt, ; Thomas, , ; Winke, ). The pedagogical implication is that L2 students should be encouraged to use multiple strategies flexibly and effectively in an enriched, multimodal learning environment, as the ability to use metacognitive strategies can be improved through strategy instruction (Ulambayar, ).…”
Section: Literature Reviewmentioning
confidence: 99%